Eesti haruldaste haiguste arengukava koos tegevusplaaniga aastateks 2015–2017 - Tillmann, Vallo; Talvik, Tiina; Teek, Rita; Joost, Kairit; Talvik, Inga; Mikkel, Sirje; Lüüs, Siiri-Merike; Stelmach, Tiina; Gross-Paju, Katrin; Sander, Valentin; Habicht, Anneli; Sõukand, Renata; et al. (Eesti Arst, 2014)
Eesti Arst 2014; 93(5):291–295